Pertarungan Kuasa dalam Wacana Islam Nusantara - Ahmad Khoirul Fata; Moh. Nor Ichwan (Islamica: Jurnal Studi Keislaman, 2017)
This article examines power struggle in the discourse of Islam Nusantara which becomes very popular in contemporary Indonesian Islam. The idea of Islam Nusantara is not different from Islam in general, but with distinctive charactericstics, such as tawâzun, i‘tidâl, and tawassut}. The proponents of this idea claim that their intellectual framework is based on the principle of maslah}ah mursalah, istih}sân, and ‘urf. Using critical discourse analysis, this article attempts to see the other side of Islam Nusantara discourse. This study is based on an assumption that language and discourse are not only an instrument to convey ideas, but also a means to construct social reality. Social activities are always related to and constructed by their social settings. This article argues that the discourse of Islam Nusantara emerges as a part of struggle for influence between mainstream Islamic movements, such as Nahdlatul Ulama and Muhammadiyah, and new transnational Islamic movements, such as Tarbiyah, Hizbut Tahrir, and Salafis. The use of the term Islam Nusantara is indeed the effort of mainstream Islamic movements to create the image of indigenous Islamic movements, different from the newly imported Islamic movements. However, the discourse of Islam Nusantara seems to be reductionist and monolithic in perceiving diverse realities of Islam in Nusantara.